MANAJEMEN EKSTRAKURIKULER COLSTRA (COLLABORATION OF MODERN MUSIC AND TRADITIONAL) DI MAN 4 JAKARTA - Puput Prabowo, Yosep Celltha; Herdiati, Dian; Saryanto (Program Studi Pendidikan Musik, 2023)
The purpose of this research is to find out and describe the management of COLSTRA (Modern Music and Traditional Collaboration) extracurricular at Madrasah Aliyah Negeri 4 Jakarta. This research method uses descriptive qualitative. Collecting data by interview, literature study, and documentation. This research was conducted from September 2022 to December 2022 at MAN 4 Jakarta. Data validation uses triangulation techniques. The results indicate that the COLSTRA extracurricular has managed well by paying attention to management functions including planning, organizing, actuating, and controling. Planning carried out by COLSTRA extracurricular includes recruiting members and trainers, planning extracurricular organizational structures, making activity plans that contain work programs, submitting inventories, and designing extracurricular budget costs, and scheduling training in a structured manner. Organizing carried out by the COLSTRA extracurricular is to distribute tasks to divisions in the organizational structure according to authority and responsibility. Basic leadership training is also carried out so that new members and new management can practice their leadership attitudes. COLSTRA extracurricular implementation conforms to plans that have been prepared. Actuating is carried out by utilizing existing facilities and infrastructure and budget costs that have been planned. Controling is carried out by the COLSTRA extracurricular, namely the extracurricular coordinator monitors the sustainability of the extracurricular and conducts training evaluations, organizational evaluations, and final evaluations for extracurricular members. Supervision of extracurricular activities is carried out by looking at COLSTRA's achievements and participation in various activities. Controlling and evaluation activities are carried out so that the extracurricular continues to develop well.